2020
DOI: 10.1101/2020.04.14.20063958
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Rapidly Deployable Negative Pressure Enclosure for Aerosol-Generating Medical Procedures

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…The most common method to assess the device's ability to contain particles or prevent contamination was through the visual assessment of droplets or smoke (71%, n = 39/55), primarily with box systems (51%, n = 20/39). Four studies used the ability to smell [ 78 , 79 ] or taste a bitter solution [ 60 , 80 ] as a proxy for aerosols escaping into the environment. Using these qualitative methods, studies concluded that the use of a barrier device was effective at either preventing or reducing the number of particles escaping the system.…”
Section: Resultsmentioning
confidence: 99%
“…The most common method to assess the device's ability to contain particles or prevent contamination was through the visual assessment of droplets or smoke (71%, n = 39/55), primarily with box systems (51%, n = 20/39). Four studies used the ability to smell [ 78 , 79 ] or taste a bitter solution [ 60 , 80 ] as a proxy for aerosols escaping into the environment. Using these qualitative methods, studies concluded that the use of a barrier device was effective at either preventing or reducing the number of particles escaping the system.…”
Section: Resultsmentioning
confidence: 99%
“…SARS-CoV-2 transmission is believed to occur primarily through close contact via respiratory droplets produced during talking, coughing or sneezing (CDC 2020a; WHO 2020). Engineering controls implemented to prevent disease transmission during the COVID-19 pandemic include separation (CDC 2020f; OSHA 2020); novel "intubation boxes" to protect healthcare workers from droplet exposure during aerosol generating procedures such as endotracheal intubations and extubations (Chahal et al 2020;Le et al 2020); and local exhaust source controls such as the ventilated headboard to protect against droplet and aerosol dissemination (CDC 2020c; Dungi et al 2015;Mead et al 2012). With a few exceptions, studies of the effectiveness of intubation boxes and local exhaust source controls are limited, and minimal guidance is available on design dimensions, deployment requirements, and in particular, on the expected performance and limitations of these systems.…”
Section: Covid-19 and The Workplace: Research Questions For The Aerosmentioning
confidence: 99%
“…Aerosol containment enclosure (ACE) is a combination of modified intubation box with a provision for negative suction. [ 31 ] It comprises a silicone gasket with arm ports for the main operator and an assistant. The size of the gasket is wide enough to suit a wide range of patients.…”
Section: Introductionmentioning
confidence: 99%
“…ACE with negative pressure has been shown to contain airborne particles in a simulation study. [ 31 ]…”
Section: Introductionmentioning
confidence: 99%